Impulse Response to Exchange Rate, Exports and Imports Shocks in Kenya 1990-2023 - Wainaina, Martin (International Journal of Economics, 2025)
Purpose: This paper explores the trend of exchange rates over the past three decades, forecasts future trends, and investigates the impulse response of exports and imports on exchange rate shocks in Kenya. The study utilizes time series (1990-2022) data from the Central Bank of Kenya (CBK) and the World Development Indicators (WDI). Methodology: The study employs the Structural VAR (SVAR) model, Vector Error Correction (VECM) model, and Impulse Response (I.R.) analysis to analyze the pass-through effect of exchange rate shocks on exports and imports in Kenya. Findings: The results of VECM highlighted a long-term relationship between exchange rates, GDP growth, Inflation, and trade volumes. Moreover, the Impulse Response Analysis revealed no instantaneous pass-through effect on imports and exports. However, an appreciation of the Kenyan Shilling led to a significant negative pass-through effect on the volume of imports. Further, the results indicated a one-way causality between the exchange rate and GDP growth rate. Also, the exchange rate and Inflation rate have a one-way granger causality. Moreover, the exchange rate Granger causes the volume of exports, while the volume of Imports Granger causes the exchange rate and the GDP growth rate Unique Contribution to Theory, Practice and Policy: The study findings emphasize the importance of stable exchange rate policies to mitigate negative impacts on trade. Policymakers should consider strategies to enhance export performance, reduce trade imbalances, and strengthen the economy's resilience to exchange rate fluctuations.